Nutritional enrichment of traditional complementary foods using underutilized nutritious plant foods in sub-Saharan Africa: their nutritional potential and health benefits: A scoping review - Diriba Chewaka Tura; Tefera Belachew; Dessalegn Tamiru; Kalkidan Hassen Abate (Applied Food Research)
Traditional complementary foods (TCFs) in sub-Saharan Africa (SSA) majorly comprised of starchy foods such as maize, sorghum, wheat, cassava and millet which are energy and nutrient deficient. This review summarizes the existing evidence on the potential of incorporating nutritious underutilized plant foods into TCFs with the application of common processing methods to enhance the nutritional value of the resultant complementary foods in SSA. Online web databases; Google Scholar, Web of Science, Scopus, and PubMed were searched, and the articles retrieved were screened using the inclusion and exclusion criteria. The review revealed that maize; apredominant stable crop used for the formulation of complementary food was enriched with amaranth, moringa and baobab that resulted in the enhancement of protein, iron, calcium, zinc, phosphorus, magnesium, copper, iodine, manganese and potassium. Enrichment of sorghum with amaranth, spinach and pigeon pea reported to enhance protein, energy, fats, calcium, iron, potassium and zinc of the resultant complement products. Cassava enriched with pigeon pea, Bambara groundnut, moringa and cowpea; wheat with quinoa, lupine, amaranth, orange-fleshed sweet potato, groundnut, mango and spinach; oats with soybean, linseed and premix (moringa leaf powder, fenugreek); teff enriched with pea, sesame, soybean, chickpea and spinach. Fermentation, germination and roasting were the most processing methods used. In conclusion, the enrichment of TCFs with underutilized plant foods combined with simple processing has proven to enhance the nutritional potential, especially protein and key micronutrients. Nutritionally adequate complementary foods could be developed using such food-based approaches to alleviate child malnutrition in SSA sustainably.